Papers - New York Meeting – February, 1929 - Equilibrium Relations in Aluminum-magnesium Alloys of High Purity - E. H. Dix; F. Keller (The American Institute of Mining, Metallurgical, and Petroleum Engineers, 1929)
The use of magnesium as an alloying element in aluminum alloys has been limited, in general, to comparatively small quantities. In duralumin-type, strong aluminum alloys, magnesium is present to the extent of 35 to 3/4 per cent. and various grades of Magnalite and the "Y" alloy of the National Physical Laboratory of England contain up to 1 1/2 per cent. In this country small quantities of aluminum alloy sheet containing 4 per cent. magnesium are produced commercially. All commercial aluminum contains sufficient silicon to convert a portion of the magnesium added to the compound Mg2Si. It is well known that the solubility of both magnesium and magnesium-silicide decrease with decrease in temperature. It is, therefore, impossible to separate the age-hardening effect of the magnesium-silicide from that of magnesium, except by the use of aluminum of such high purity that the silicon content is negligible. The present paper is the fifth l, 2, 3, 4 of a series from the laboratories of the Aluminum Co. of America reporting the results of investigations of the equilibrium relations in aluminum-rich alloys made from the high-purity aluminum manufactured by this company. 5 Previous Investigations A number of investigations have been made of the constitution of the complete aluminum-magnesium system and several determinations made